Lysosomal glycogen accumulation in Pompe disease results in disturbed cytoplasmic glycogen metabolism. Issue 1 (17th October 2022) - Canibano‐Fraile, Rodrigo; Harlaar, Laurike; dos Santos, Carlos A.; Hoogeveen‐Westerveld, Marianne; Demmers, Jeroen A. A.; Snijders, Tim; Lijnzaad, Philip; Verdijk, Robert M.; van der Beek, Nadine A. M. E.; van Doorn, Pieter A.; van der Ploeg, Ans T.; Brusse, Esther; et al.
Abstract: Pompe disease is an inherited metabolic myopathy caused by deficiency of acid alpha‐glucosidase (GAA), resulting in lysosomal glycogen accumulation. Residual GAA enzyme activity affects disease onset and severity, although other factors, including dysregulation of cytoplasmic glycogen metabolism, are suspected to modulate the disease course. In this study, performed in mice and patient biopsies, we found elevated protein levels of enzymes involved in glucose uptake and cytoplasmic glycogen synthesis in skeletal muscle from mice with Pompe disease, including glycogenin (GYG1), glycogen synthase (GYS1), glucose transporter 4 (GLUT4), glycogen branching enzyme 1 (GBE1), and UDP‐glucose pyrophosphorylase (UGP2). Expression levels were elevated before the loss of muscle mass and function. For first time, quantitative mass spectrometry in skeletal muscle biopsies from five adult patients with Pompe disease showed increased expression of GBE1 protein relative to healthy controls at the group level. Paired analysis of individual patients who responded well to treatment with enzyme replacement therapy (ERT) showed reduction of GYS1, GYG1, and GBE1 in all patients after start of ERT compared to baseline. These results indicate that metabolic changes precede muscle wasting in Pompe disease, and imply a positive feedforward loop in Pompe disease, in which lysosomal glycogen accumulation promotes cytoplasmic glycogen synthesis and glucose uptake, resulting in aggravation of the disease phenotype. Abstract :